Crucial role of antibodies to pertactin in Bordetella pertussis immunity - Hellwig, Sandra M. M. (2003)
Pertussis, a serious infectious disease of the respiratory tract caused by Bordetella pertussis, is reemerging in vaccinated populations. Efforts to curtail this disease are hampered by limited insight into the basis of protective immunity. Opsonophagocytosis was recently found to play a central role in cellular bactericidal activity against B. pertussis. In the present study, we studied the specificity of opsonic antibodies. Anti-pertactin antibodies, but not anti-pertussis toxin, anti-fimbriae, or anti-filamentous hemagglutinin antibodies, were found to be crucial for B. pertussis phagocytosis. These data are consistent with field studies showing that levels of antibodies to pertactin correlate with protection.